Mitigating Heavy Metal Contamination in Agricultural Soils with Biosilica-Humic Acid as Soil Amendment Strategies in Industrial Peripheries - M Ghufron Chakim; Wanti Mindari; Purnomo Edi Sasongko (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Soil contamination by heavy metals poses a significant threat to sustainable agriculture, especially in areas adjacent to industrial zones. This study demonstrates that while the initial application of the biosilica-humic acid (BSi-HA) soil amendment did not result in statistically significant changes in soil chemical properties within the first 7 days of incubation, prolonged incubation for 60 days revealed meaningful effects, particularly in reducing heavy metal availability in soil. Significant decreases in iron (Fe) and lead (Pb) concentrations were observed over time, with Fe reductions ranging from 45–67% and Pb reductions between 8–40%. These results are attributed to the synergistic effect of functional groups in BSi-HA—especially the carboxyl (–COOH) and hydroxyl (–OH) groups in humic acid—which exhibit high metal-binding affinity under acidic conditions (pH 5). Although soil fertility parameters such as C-organic content and cation exchange capacity (CEC) showed a declining trend due to microbial activity during incubation, the ability of BSi-HA to immobilize heavy metals without exceeding safe thresholds highlights its potential as a sustainable soil amendment. Moreover, previous findings indicating reductions of up to 90% for Pb and 76% for Cd in plant tissues further support the efficacy of BSi-HA in mitigating heavy metal contamination in agricultural soils near industrial zones. Further long-term studies are recommended to evaluate BSi-HA's remediation capacity, persistence, and impact on crop yield and food safety. Combining biosilica and humic acid offers a promising, eco-friendly approach for managing heavy metal contamination in soils.